Burkholderia pseudomallei: Rare pathogen causing urosepsis in a diabetic patient - A case report (Indian Journal of Case Reports, 2018)
Burkholderia pseudomallei is soil-dwelling bacterium which causes melioidosis, a disease of tropical climates. Very few cases have been reported from the Indian subcontinent despite similarities in environmental conditions with Southeast Asian countries. Here, we report a case of acute bloodstream infection in a diabetic patient with bilateral renal calculi with bilateral hydroureteronephrosis and left gluteal cellulitis. Blood and urine samples were processed in the microbiology laboratory for culture and sensitivity. Gram stain showed short, straight Gram-negative bacilli with a